Alaska Hot Scoop Enterprise / Intan Nurbaizura Zainuddin ... [et al.] - Zainuddin, Intan Nurbaizura; Ibrahim, Juraidah; Ibrahim, Khairiah; Rosli, Noredayu; Binti Md Sarwin, Nor Fauzan; Hisham, Ranita (Faculty of Information Management, 2005)
Name of the company: Name of our company is Alaska Hot Scoop Enterprise. • Nature of business: Our business is based food manufacturing and distributing the products. • Industry profile: Our business is owned actively by partnership, incorporated as an Alaska Hot Scoop Enterprise. As a small startup company, we recognize the limitation of attempting to manufacture our products in a small premise. So that, our companies can more concentrate on making the products, as well as give good services to produce our products based on our customer demand. • Location of the business: Our business is locates at Giant Hypermarket at Senawang. We choose this location because it is situated in the center area of people passage from every place in Senawang. • Date of the business commencement: Our business will begin to operate on 1st January 2006.